FBXW7 and Its Downstream NOTCH Pathway Could be Potential Indicators of Organ-Free Metastasis in Colorectal Cancer - Li, Dongzheng; Jiang, Shiye; Zhou, Xin; Si, Chengshuai; Shao, Peng; Jiang, Qian; Zhu, Liuqing; Shen, Lu; Meng, Qi; Yin, Jiani C.; Shao, Yang; Sun, Yueming; et al. (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the leading causes of cancer-related death globally. Metastasis is associated with a poor prognosis, yet the underlying molecular mechanism(s) remained largely unknown. In this study, a total of 85 CRC patients were included and the primary tumor lesions were evaluated by next-generation sequencing using a targeted panel for genetic aberrations. Patients were sub-divided according to their metastasis pattern into the non-organ metastases (Non-OM) and organ metastases (OM) groups. By comparing the genetic differences between the two groups, we found that mutations in FBXW7 and alterations in its downstream NOTCH signaling pathway were more common in the Non-OM group. Moreover, correlation analysis suggested that FBXW7 mutations were independent of other somatic alterations. The negative associations of alterations in FBXW7 and its downstream NOTCH signaling pathway with CRC organ metastasis were validated in a cohort of 230 patients in the TCGA CRC dataset. Thus, we speculated that the genomic alterations of FBXW7/NOTCH axis might be an independent negative indicator of CRC organ metastases.